2023
DOI: 10.3390/genes14040881
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Functional Genes and LncRNAs Influencing Muscle Growth and Development in Leizhou Black Goats

Abstract: Meat yield and quality are important economic traits of livestock. Herein, longissimus dorsi (LD) muscles of Leizhou black goats aged 0, 3, and 6 months were used to identify differentially expressed messenger RNAs (mRNAs) and long non-coding RNAs (lncRNAs) by high-throughput RNA sequencing. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were used to analyze differentially expressed genes. Expression levels of regulator of calcineurin 1 (RCAN1) and olfactory receptor 2AP1 (OR2AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Skeletal muscle requires a great deal of energy and proteins to develop [ 50 ]. It has been reported that skeletal muscle hypertrophy requires an increase in the rate of protein synthesis, and one way in which this can be achieved is by increasing the translational capacity of muscle through ribosome biogenesis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle requires a great deal of energy and proteins to develop [ 50 ]. It has been reported that skeletal muscle hypertrophy requires an increase in the rate of protein synthesis, and one way in which this can be achieved is by increasing the translational capacity of muscle through ribosome biogenesis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the categories "translation, ribosomal structure and biogenesis (13~27.66%)" and "energy production and conversion (12~25.53%)" were highly enriched according to COG classifications, which included the 154 highly expressed DEGs (FPKM > 10) of F0 vs. N0 (Figure 17B). Skeletal muscle requires a great deal of energy and proteins to develop [50]. It has been reported that skeletal muscle hypertrophy requires an increase in the rate of protein synthesis, and one way in which this can be achieved is by increasing the translational capacity of muscle through ribosome biogenesis [51].…”
Section: Myogenesis Progresses More Slowly In Fqs Than In Nbysmentioning
confidence: 99%
“…In recent years, numerous RNA-seq studies have investigated the growth performance of livestock and poultry. These studies aim to uncover the molecular mechanisms that regulate their growth traits ( Qian et al, 2023 ; Zhang et al, 2023 ; Zhao et al, 2023 ). Hu et al (2022) found that short photoperiod significantly promoted muscle development and significantly improved the redness of goose muscle, and identified the possible involvement of glycolysis/gluconeogenesis, calcium signaling pathway, and PI3K-Akt signaling pathway in the regulation of muscle development and meat color in geese by light through RNA-seq analysis.…”
Section: Introductionmentioning
confidence: 99%